The use and effectiveness of Facebook in small-scale volunteer organisation for refugee children’s education in Malaysia - Shekaliu, Sahar; Mustafa, Siti Ezaleila; Hamedi, Mohd Adnan; Guajardo, Jarret (Taylor's University College, 2018)
How is a small-scale volunteer organization in Malaysia utilizing Facebook to engage the Malaysian public in volunteer work for refugee children’s education? This paper addresses this question by investigating the social media use of “Let’s Tutor a Refugee Child”. By using quantitative content analysis and social media analytics, this study analyzes the Facebook use on both message level and organization level. This study found that there is a salient divide between the different types of social media content and the interaction created online. It also found that the prevalence of advocacy messages based on the social media advocacy pyramid is very different. Over half of the all Facebook posts by volunteer organization fall into the “Information” category, followed by the “Action” category. “Community-building” posts seem to be neglected. With regards to the effectiveness of social media, this study found that (a) although volunteer organizations have managed to reach a significant number of members; they have failed to keep their members active on social media, (b) volunteer organization are not fully exploiting dialogical affordance of social media, and (c) volunteer organization have failed to get more members stepping up to action. This study contributes to social media literature by integrating different theories to show the utilization of social media by small-scale volunteer organizations.